Syndecan-1 as a therapeutic target in squamous cell carcinoma: Current insights and future directions - Rita Files, Cláudia Cardoso, Justina Prada, Filipe Silva, Isabel Pires (Journal of Applied Pharmaceutical Science, 2025)
Squamous cell carcinoma (SCC) is a type of epithelial cancer that originates in the squamous epithelium and can develop in any area of the body covered by this tissue. Cutaneous SCC is characterized by a locally aggressive tumor, highlighting the importance of identifying new therapeutic targets to combat this disease effectively. Syndecan-1, a molecule often deregulated in cutaneous SCC, is a type 1 transmembrane proteoglycan primarily expressed in epithelial and plasma cells. The ectodomain of Syndecan-1 is frequently shed, rendering the molecule soluble and capable of interacting with various other molecules. This review aims to comprehensively analyze Syndecan-1 expression in cutaneous squamous cell carcinoma (CSCC), elucidate its role in tumorigenesis, and assess promising therapeutic strategies that target Syndecan-1 and its associated pathways. Therapeutic approaches often focus on molecules that facilitate the shedding of the Syndecan-1 ectodomain, such as matrix metalloproteinases (MMPs) and heparanase. Inhibition of heparanase and MMPs has shown potential in preventing the degradation of Syndecan-1 and reducing tumor invasiveness. Additional strategies include using synthetic proteoglycans, peptide mimetics such as syntenin, and overexpression of the C-terminal fragment of Syndecan-1 to suppress tumor growth and migration. Moreover, targeting microRNAs that regulate Syndecan-1 expression presents another promising therapeutic tool. These therapies are designed to modulate the function of Syndecan-1, potentially affecting the progression of CSCC and improving clinical outcomes.
Keywords: Syndecan-1, therapeutic target, cancer, cutaneous squamous cells carcinoma, biomarker